Spontaneous rupture of incisional hernia: a rare cause of a life-threatening complication. (3rd March 2011) - Gupta, R K; S, Sah; S C, Agrawal
Abstract : Spontaneous evisceration is a very rare and potentially fatal complication of abdominal-wall incisional hernia. Here the authors present a case report of spontaneous evisceration in an incisional hernia in a 45-year-old female patient. Management of the condition using prosthetic mesh repair risks mesh infection, while the use of non-prosthetic repair risks recurrence of the hernia due to the absence of stout natural tissues. Use of a biological mesh for the condition seems quite plausible. Thorough saline washes of the eviscerated organ; excision of redundant/unhealthy skin and strict adherence to the fundamental principles of hernia repair is desired in managing the condition.